Why are males inclined to use strong swear words more than females? An evolutionary explanation based on male intergroup aggressiveness. (July 2015) - Güvendir, Emre
Abstract: The research on sex differences in terms of the use of strong swear words show that males have the inclination to utter strong swear words and to display aggressive actions more than females. Correspondingly, recent discoveries stress that females have larger volumes of orbital frontal cortex that modulates anger and aggressiveness created by the amygdala which might be related to sex differences in the use of strong swear words. Based on these findings, this study explores what kind of environmental and social pressures might have fashioned strongly swearing aggressive males during the course of human evolutionary history and examines the evolution of swearing by discussing the possible factors that might have prompted its emergence in our evolutionary background. Highlights: Sex-related structural differences in the human brain. Males swear more than females. Sex differences in the environment likely have major effects on brain biology. Males are more aggressive than females.